mTeSR1 is beneficial for the early development of bovine embryos and promotes the proliferation of the inner cell mass during the outgrowth of blastocysts - Dohyun Kim; HakKyo Lee; Dae-Jin Kwon (Journal of Animal Reproduction and Biotechnology)
Background: mTeSR1 is a fully-defined, serum-free medium for the derivation and maintenance of Human embryonic stem cells (ESCs). This study investigates the impact of incorporating mTeSR1 supplement during in vitro culture (IVC) on blastocyst productivity, qualitative characteristics, and outgrowth potential of bovine blastocysts. Methods: In vitro fertilized (IVF) eggs were cultured in IVC medium (control) with the addition of mTeSR1 supplement at concentrations of 1%, 2%, and 5%, respectively. The development rates of fertilized eggs and gene expression patterns of blastocysts were assessed on day 9 of culture. For outgrowth culture, blastocysts were cultured on a mouse embryonic fibroblast feeder cells (MEFs) for 7 days. Results: In vitro development of bovine preimplantation embryos in the 2% mTeSR1 group was significantly higher than in the control (p < 0.05). The apoptotic index in the 2% mTeSR1 group was significantly lower compared to the control (p < 0.05). RTqPCR indicated that SRY-Box Transcription Factor 2 (Sox2) gene expression in the 5% mTeSR1 group was significantly higher than in the control (p < 0.05). The 5% mTeSR1 group also showed significantly higher BCL2 associated X (Bax) expression compared to the control and other mTeSR1 groups. On day 9 pi, blastocysts from the control and 2% mTeSR1 groups were cultured for 7 days. The 2% mTeSR1 group showed higher efficiency in forming dome-shaped colonies with stronger SOX2 expression compared to the control. Conclusions: The mTeSR1 supplement supports preimplantation embryo development and prevents apoptosis in blastocysts, leading to the efficient formation of domeshaped inner cell mass (ICM) colonies.